Pengaruh Ukuran Perusahaan, Earning Per Share dan Return On Asset Terhadap Nilai Perusahaan Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2018 - Cheltis Charles Kehek; Wayan Cipta; Ni Made Suci (Jurnal Akuntansi Profesi, 2021)
This study aims to examine the effect of company size, earnings per share and return on assets on the value of the food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2016 - 2018 either simultaneously or partially. The population used in this research is the food and beverage sub sector companies listed on the Indonesia Stock Exchange for the period 2016 - 2018 as many as 11 companies. The research design used is quantitative causal. Data were collected by recording documents, and analyzed by multiple linear regression analysis. The results of this study indicate that: (1) company size, earnings per share, and return on assets have a significant effect on firm value .(2) company size partially has a positive and significant effect on firm value.(3) Earning per share has a negative and significant effect on firm value. (4) Return on assets has a positive and significant effect on firm value.